Collaborative Translation of Knowledge to Protect Infants During Sleep: A Synergy of Discovery and Practice. Issue 4 (22nd November 2017) - Middlemiss, Wendy; Cowan, Stephanie; Kildare, Cory; Seddio, Kaylee
Abstract : The impact of discoveries from scientific research is manifested in its timely application to real‐world conditions, with a goal of improving life. This is the desired research‐to‐practice transition for new knowledge, yet it is not always achieved. Where knowledge is simply transferred in its discovered form, there can be unintended consequences and harmful delays in achieving desired changes if there is not also a cultural and contextual fit with targeted populations. This has been the case, for example, in the failure of the "don't bedshare" message in protecting African American infants, a message derived from the discovery of heightened risk of death for infants who sleep in the same bed as others. Knowledge transfer implies movement in one direction: from researchers to end‐users. Family scientists, who work with families, understand that knowledge in its discovered form needs to be translated, and not just transferred, if it is to be useful to families and fit with their values, preferences, and circumstances. Unlike knowledge transfer, knowledge translation is bidirectional, with multiple informants, including but not limited to the new discoveries themselves. In this article, we examine the history of discovery and practice as it relates to preventing sudden infant death. Using safer infant sleep as an example, this review demonstrates the importance of collaborative translation between discovery and practice for developing health policies, interventions and messaging that are enabling for all families.